PERAN TIM PENGAWAL DAN PENGAMANAN PEMBANGUNAN DAN PEMERINTAHAN DAERAH (TP4D) DALAM PENGADAAN BARANG DAN JASA PEMERINTAH (Studi Di Kejaksaan Tinggi Kalimantan Barat). - DENI SUSANTO, SH NPM.A2021151068, Jurnal Mahasiswa s2 Hukum Untan (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACT This thesis discusses the role of guard and security team of development and local government (TP4D) in procurement of government goods and services (Study At West Kalimantan High Prosecutor). The method used in this research is Normative-Sociological approach. The conclusion of this thesis is that the formation of the Guard and Security Team for the Government and Regional Development (TP4D) of the High Prosecutor of West Kalimantan based on the Decree of the Attorney General of the Republic of Indonesia Number: KEP-152 / A / JA / 10/2015 dated October 1, 2015 on the Formation of Team Guards and Security of Governance and Development of the Attorney of the Republic of Indonesia which has the duty of: Guarding, securing and supporting the success of government and development through preventive / preventive and persuasive efforts in the legal area of the West Kalimantan High Prosecutor by: A) To provide legal information in the environment of government agencies, SOEs, BUMDs and other parties related to materials on planning, auctions, execution of work, supervision of the implementation of work, licensing, procurement of goods and services, administrative order and State finance management; B) Conducting discussion or discussion with government agencies, SOEs, BUMD to identify problems encountered in the absorption of budget and development implementation; C) Providing legal information and legal counseling both on the TP4D initiative and at the request of the discriminating parties to which the place and time of implementation is determined by agreement and as required; D) TP4D may involve agencies or other parties who have the capacity, competence and relevant with legal information material to be submitted to government agencies, SOEs and BUMD. Can provide legal assistance in each stage of the development program from beginning to end, in the form of: Legal discussion from the side of the application of regulations, legislation, mechanisms and procedures with budget managers over the problems faced in terms of budget absorption, Legal opinions in the planning stages, Auctions, execution of work, supervision of work implementation, licensing, procurement of goods and services on the initiative of TP4D as well as on request of instasi and parties in need. Coordinate with the Government Internal Supervisory Apparatus to prevent potential irregularities that inhibit, thwart, and cause harm to State finances; Together to monitor and evaluate the implementation of work and development programs;Carry out repressive law enforcement when sufficient preliminary evidence is found after coordination with the Government Internal Supervisory Apparatus regarding the occurrence of unlawful acts, misuse of authority and / or other acts that result in harm to the State's finances. The constraints faced by the Guard and Security Team Development and Local Government (TP4D) in relation to the procurement of goods and services of the High Prosecutor's Office of West Kalimantan is the lack of government coordination with the Attorney General especially in the case of legal assistance and enforcement by the Attorney General during the Budget Planning Meeting. Passive and Apathetic Communities during the Public Prosecution Service. Keywords: Role, Security Guard Team for Development and Local Government, Procurement, Services Goods. 2 ABSTRAK Tesis ini membahas tentang peran tim pengawal dan pengamanan pembangunan dan pemerintahan daerah (TP4D) dalam pengadaan barang dan jasa pemerintah (Studi Di Kejaksaan Tinggi Kalimantan Barat). Metode yang digunakan dalam penelitian ini adalah pendekatan Normatif-Sosiologis. Adapun kesimpulan dari tesis ini ada bahwa Bahwa pembentukan Tim Pengawal dan Pengaman Pemerintahan dan Pembangunan Daerah (TP4D) Kejaksaan Tinggi Kalimantan Barat berdasarkan Keputusan Jaksa Agung Republik Indonesia Nomor : KEP-152/A/JA/10/2015 tanggal 1 Oktober 2015 tentang Pembentukan Tim Pengawal dan Pengaman Pemerintahan dan Pembangunan Kejaksaan Republik Indonesia yang mempunyai tugas : Mengawal, mengamankan dan mendukung keberhasilan jalannya pemerintahan dan pembangunan melalui upaya-upaya pencegahan/preventif dan persuasive di daerah hukum Kejaksaan Tinggi Kalimantan Barat, dengan cara : a) Memberikan penerangan hukum di lingkungan instansi pemerintah, BUMN, BUMD, dan pihak lain yang terkait materi tentang perencanaan, pelelangan, pelaksanaan pekerjaan, pengawasan pelaksanaan pekerjaan, perijinan, pengadaan barang dan jasa, tertib administrasi, dan tertib pengelolaan keuangan Negara; b) Melakukan diskusi atau pembahasan bersama instansi pemerintah, BUMN, BUMD untuk mengidentifikasi permasalahan yang dihadapi dalam penyerapan anggaran dan pelaksanaan pembangunan; c) Memberikan penerangan hukum dan penyuluhan hukum baik atas inisiatif TP4D maupun atas permintaan pihak-pihak yang memerllukan yang tempat dan waktu pelaksanaan ditetapkan berdasarkan kesepakatan dan sesuai kebutuhan; d) TP4D dapat melibatkan instansi atau pihak lain yang memiliki kapasitas, kompetensi dan relevan dengan materi penerangan hukum yang akan disampaikan kepada instasi pemerintah, BUMN, dan BUMD. Dapat memberikan pendampingan hukum dalam setiap tahap pogram pembangunan dari awal sampai akhir, berupa : Pembahasan hukum dari sisi penerapan regulasi, peratuan perundang-undangan, mekanisme dan prosedur dengan pejabat pengelola anggaran atas pemasalahan yang dihadapi dalam hal penyerapan anggaran, Pendapat hukum dalam tahapan perencanaan, pelelangan, pelaksanaan pekerjaan, pengawasan pelaksanaan pekerjaan, perijinan, pengadaan barang dan jasa atas inisiatif TP4D maupun atas permintaan instasi dan pihak-pihak yang memerlukan. Melakukan kordinasi dengan Aparat Pengawasan Intern Pemerintahan untuk mencegah terjadinya penyimpangan yang berpotensi menghambat, menggagalkan, dan menimbulkan kerugian bagi keuangan Negara; Bersama-sama melakukan monitoring dan evaluasi pelaksanaan pekerjaan dan program pembangunan; Melaksanakan penegakan hukum represif ketika ditemukan bukti permulaan yang cukup setelah dilakukan koordinasi dengan Aparat Pengawasan Intern Pemerintah tentang telah terjadinya perbuatan melawan hukum, penyalagunaan kewenangan dan/atau perbuatan lainnya yang berakibat menimbulkan kerugian bagi keuangan Negara.Kendala-kendala yang dihadapi oleh Tim Pengawal Dan Pengamanan Pembangunan Dan Pemerintahan Daerah (TP4D) dalam kaitannya dengan pengadaan barang dan jasa pemerintah Kejaksaan Tinggi Kalimantan Barat adalah kurangnya koodinasi pemerintah dengan Kejaksaan terutama dalam hal pendampingan dan penerangan hukum oleh pihak Kejaksaan saat Rapat Pemabahasan Anggaran. Masyarakat yang Pasif dan cenderung Apatis saat Kejaksaan melakukan Penyuluhan Hukum. Kata Kunci: Peran, Tim Pengawal Pengamanan Pembangunan DanPemerintahan Daerah, Pengadaan, Barang Jasa.